Criminal obsessions: Why harm matters more than crime - Dorling, D; Gordon, D; Hillyard, P; Pantazis, C; Pemberton, S; Tombs, S (Centre for Crime and Justice Studies, 2008)
Criminal obsessions is an innovative, groundbreaking critique of conventional criminological approaches to social issues. The contributors show how social harm relates to social and economic inequalities that are at the heart of the liberal state. This second edition of Criminal obsessions includes an additional essay by Simon Pemberton in which he develops theoretically the concept of social harm and discusses the future of the social harm perspective. Contributors to the edited collection include Danny Dorling, Dave Gordon, Paddy Hillyard, Christina Pantazis, Simon Pemberton and Steve Tombs.